Migraciones de ayer y de hoy Perspectivas y nuevos desafíos - Eugenia Cruset, Maria; Ruffini, Martha E. (Internacional del Conocimento, 2022)
At present, the interrelation of people, countries and cultures is undeniable. The advances in communications, the greater facility in the transfer of people, merchandise and capital; but also the supranational institutional advances resulting from globalization have generated phenomena rarely seen before and that require new tools for their analysis. Our intention in bringing together the different contributions was to offer a range of issues and problems that do not exhaust the increasingly broad and complex agenda of problems arising from migratory groups. But we believe that the quality and diversity of the works presented here undoubtedly constitute a valuable contribution to the production of knowledge and the scientific debate about the construction of citizenship in a global world.